2009
DOI: 10.1111/j.1365-3059.2009.02043.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of competition and host plant resistance on selection in Phytophthora infestans populations in Michigan, USA and in Northern Ireland

Abstract: Competition between genotypes of Phytophthora infestans was studied by inoculating potato cultivars with differing susceptibility to late blight in field experiments over three years in Northern Ireland, UK, and Michigan, USA. Multiple isolates of six genotype groups of P. infestans were chosen from the local populations in both N. Ireland and Michigan for inoculation of separate field trials planted in 2003, 2004 and 2005. Four cultivars were used in each trial; two (susceptible cv. Atlantic and the partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 39 publications
(61 reference statements)
2
23
0
2
Order By: Relevance
“…P. taxon PgChlamydo which was detected in high frequency (59.72% of all isolates), is also frequently isolated from streams, rivers, irrigation water and soils in western North America, Argentina, Europe and Australia (Brasier et al 1993;Hansen and Delatour 1999;Greslebin et al 2005;Burgess et al 2009;Reeser et al 2011a,b). Extreme selection occurred within the population of genotypes of P. infestans in North Ireland in each year with different genotype groups dominating the infection of different resistant potato cultivars (Young et al 2009). The abundance of Phytophthora species and strains might result from the high diversity of forest vegetation, stands and environment in mountainous areas.…”
Section: Distribution Of Phytophthora Speciesmentioning
confidence: 99%
“…P. taxon PgChlamydo which was detected in high frequency (59.72% of all isolates), is also frequently isolated from streams, rivers, irrigation water and soils in western North America, Argentina, Europe and Australia (Brasier et al 1993;Hansen and Delatour 1999;Greslebin et al 2005;Burgess et al 2009;Reeser et al 2011a,b). Extreme selection occurred within the population of genotypes of P. infestans in North Ireland in each year with different genotype groups dominating the infection of different resistant potato cultivars (Young et al 2009). The abundance of Phytophthora species and strains might result from the high diversity of forest vegetation, stands and environment in mountainous areas.…”
Section: Distribution Of Phytophthora Speciesmentioning
confidence: 99%
“…This suggests that the genes responsible for foliage resistance are not present or at least active in the tubers. Inoculation with the US-8 genotype of P. infestans, the dominant genotype in North America (Young et al 2009), resulted in significant tuber late blight development for most cultivars and ABL tested. These findings are in agreement with Lambert and Currier (1997) and Lambert et al (1998) who found that the US-8 genotype isolates were the most ) circumstantially suggest that highly aggressive genotypes of P. infestans, such as the US-8 genotype, may produce limited primary inoculum due to severe tuber rotting and deterioration of tubers before emergence.…”
Section: Discussionmentioning
confidence: 97%
“…Cultures of P. infestans isolates corresponding to clonal lineages US-1 (Pi95-3), US-1.7 [Pi88 (2002-06) (Young et al 2009). The selected isolates were from the collection of W. Kirk (Michigan State University).…”
Section: Culturing Of Phytophthora Infestans and Tuber Inoculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of P. infestans in the northeastern US have been extensively characterized, but Michigan populations have never been comprehensively studied. Nonetheless, some recent studies have published characteristics of a few P. infestans isolates collected in Michigan (Young et al, 2009;Catal et al, 2010). The clonal lineage US-1 of P. infestans was present from before 1991 until around 1995, when the population shifted to clonal lineage US-8 (Kirk et al, 2004).…”
Section: Introductionmentioning
confidence: 99%